Effects of sodium, chloride, and sodium metabisulfite in nursery and grow-finish pig diets - Shawk, Dwight Jay (Kansas State University, 2018)
A total of 12,229 pigs were used in nine experiments to determine the effects of Na, Cl, and sodium metabisulfite-based feed additives on pig growth performance. Experiments 1, 2, and 3 were conducted to determine the effects of added dietary salt on growth performance of pigs weighing 7 to 10, 11 to 30, and 27 to 65 kg. The BLL models suggested the optimal dietary added salt concentration to maximize ADG for pigs weighing 7 to 10 and 11 to 30 kg was 0.59% (0.34% Na and 0.58% Cl) and 0.51% added salt (0.22% Na and 0.42% Cl), respectively. There was no evidence to indicate that growth of 27 to 65 kg pigs was improved beyond a 0.10% added salt inclusion (0.11% Na and 0.26% Cl). Experiments 4, 5, and 6 were conducted to determine the effects of source and concentration of Na and Cl on the growth performance of pigs weighing 7 to 12 kg. In Exp. 4, pigs fed an added salt diet that contains a Na and Cl concentration of 0.35% and 0.60% had greater growth performance compared to pigs fed a deficient Na concentration of 0.18%. In Exp. 5, pigs fed a Na concentration of 0.35%, regardless of ion source, had improved ADG compared to pigs fed a Na concentration of 0.13% or 0.57%. In Exp. 6, maximum ADG and G:F could be obtained with a Cl concentration of 0.38% based on the BLL and QP models. Experiments 7, 8, and 9 were conducted to evaluate the effects of Product 1 (Provimi, Brooksville, OH), Product 2 (Nutriquest, Mason City, IA), and sodium metabisulfite (SMB) on the growth performance of nursery pigs weighing approximately 6 to 25 kg. In Exp. 7, pigs fed Product 1 had higher ADG compared to pigs fed the control. In Exp. 8, pigs fed either Product 1 or 2 at the highest concentration and for the longest period of time had greater ADG compared to pigs fed the control diet. In Exp. 9, pigs fed SMB or Product 1 had greater ADG compared to pigs fed a lower concentration of SMB and the control.
Keywords: Chloride; Growth; Pig; Salt; Sodium; Sodium metabisulfite